SOCIAL DATA ANALYSIS USING BIG-DATA ANALYTIC TECHNOLOGIESAPACHE FLUME, HDFS, HIVE. - Panigrahi, Ms.Sulochana; Kumar, Dr.S Mohan (IJRDO -Journal of Computer Science Engineering, 2016)
Analysis on Social media data is difficult due to language that is used for comments. For this analysis using Hive and its queries to give the sentiment data based up on the groups that defined in the HQL (Hive Query Language) is utmost important and so much in demand. The analysis can be positive, moderate and negative comments. Tools can be used to do the analysis are: Apache Flume, HDFS, Hive. In this paper all related research works and Bigdata Tools, technologies and observations from the survey are all presented for better understanding.